CELES: CUDA-accelerated simulation of electromagnetic scattering by large ensembles of spheres. (September 2017) - Egel, Amos; Pattelli, Lorenzo; Mazzamuto, Giacomo; Wiersma, Diederik S.; Lemmer, Uli
Abstract : Hihglights: A new, freely available MATLAB software for light scattering by large ensembles of spheres is introduced. It uses block-diagonal preconditioning, a lookup-table approach for the evaluation of costly functions and parallel execution on the GPU via NVIDIA's CUDA platform. The validity of the results is demonstrated by comparison to established software. The convergence behavior for scattering by large aggregates is discussed. An accurate simulation of scattering by 100, 000 wavelength-scale spheres is demonstrated. Abstract: CELES is a freely available MATLAB toolbox to simulate light scattering by many spherical particles. Aiming at high computational performance, CELES leverages block-diagonal preconditioning, a lookup-table approach to evaluate costly functions and massively parallel execution on NVIDIA graphics processing units using the CUDA computing platform. The combination of these techniques allows to efficiently address large electrodynamic problems (>10 4 scatterers) on inexpensive consumer hardware. In this paper, we validate near- and far-field distributions against the well-established multi-sphere T -matrix (MSTM) code and discuss the convergence behavior for ensembles of different sizes, including an exemplary system comprising 10 5 particles.